RBBP6 interactome: RBBP6 isoform 3/DWNN and Nek6 interaction is critical for cell cycle regulation and may play a role in carcinogenesis. (2021) - Mbita, Zukile; Hull, Rodney; Mokoena, Fortunate; Lai, Chin-Hung; Dlamini, Zodwa
Abstract: RBBP6 is a multidomain protein, with four splice variants translated into four functional isoforms. RBBP6 isoform 1 has been reported to interact with TP53 and pRb as well as with proteins that regulate transcriptional response to tumorigenesis such as HDM2, ZBTB38, YBX1 and NEK6. Experimental validation of isoforms 2 and 4 is yet to be conducted. The third isoform, consisting of only the DWNN domain and a short unordered c terminus, has been shown to be down-regulated in several human cancers and demonstrated as a regulator of G2/M cell cycle arrest. A number of studies have supported the role of DWNN in cell cycle regulation, however, its mechanism in these processes remains obscure. Posttranslational modification of DWNN could be critical for its function and this study was formulated to understand how the DWNN regulates the cell cycle. Our study identified 12 cell cycle-related proteins interacting with DWNN using various bioinformatics tools. We also identified 10 ubiquitin ligases that interact with DWNN. The most relevant interacting partner, the cell cycle regulator Nek6, has been reported to interact with DWNN during the cell cycle. It was therefore critical to interrogate the interaction between Nek6 and DWNN by homology modelling and docking. The DWNN mutants had a reduced affinity for NEK6 with at least one of the mutants having changes that affect at least one phosphorylation site. It is likely that NEK6 promotes cell proliferation by phosphorylating DWNN. This work suggests that DWNN co-regulates RNA splicing, ubiquitination, and cell cycle control. DWNN may therefore, be targeted for novel anticancer therapies through cell cycle regulation. Graphical abstract: Image 1